The Contributions of Ibn Malik to Arabic Language Education: A Historical and Pedagogical Analysis - Ibnu Fitrianto; Muhammad Rizqi Al-Faruqi; Nur Aisyah Hanifah (IJAS: International Journal of Arabic Studies, 2025)
Ibn Malik is a prominent figure in Arabic linguistics, best known for his monumental work, Alfiyyah Ibn Malik, which has played a crucial role in shaping Arabic grammar education. This study explores his contributions to Arabic language education from both a historical and pedagogical perspective. Using a qualitative research approach with historical and pedagogical analysis, this research examines the structure, methodology, and relevance of Alfiyyah in contemporary Arabic teaching. The findings reveal that Ibn Malik’s approach emphasizes systematic grammatical instruction, memorization, and structured sequencing of linguistic rules, making it an essential reference in traditional Arabic education. However, challenges arise when applying this method in modern pedagogical contexts, particularly for non-native Arabic learners. This study highlights the need for adaptation, suggesting that integrating technology-enhanced learning, contextual grammar instruction, and communicative approaches can enhance the effectiveness of Ibn Malik’s methodology in contemporary classrooms. The research concludes that while Alfiyyah Ibn Malik remains a cornerstone of Arabic grammar studies, modern innovations in language teaching strategies are necessary to optimize its impact for today’s diverse learners.